Purificação e caracterização parcial de um potyvirus isolado de siratro e produção de anti-soro específico - Marques, Mary Anne Lopes (1992)
A virus isolated from naturally infected plants of siratro, Macroptilium atropurpureum, grown on the Animal Science Department of the Federal University of Ceará was partially characterized according to its biological, serological and physical properties, and the cytopathological aspects of infected host. The cytopathological studies under the light microscope of infected cells indicated the presence of cytoplasmic inclusions similar to those described for the potyviruses. The virus was designated as siratro mosaic virus (SrMV). Serological tests showed that the SrMV is serologically related to blackeye cowpea mosaic virus, clitoria mosaic virus, passionfruit woodiness virus and isolates of cowpea aphid-borne mosaic virus, and serologically different from bean common mosaic and papaya ringspot viruses. The virus was able to infect systematically seven among 23 plant species studied, five of which belong to the family Leguminosae. Nicotiana benthamiana was selected for propagation and purification of the virus. In the purification procedure, a combination of chloroform and carbon tetrachloride was used in the clarification process, followed by precipitation with polyethylene glycol combined with iriton X-100. The virus was further separated from the plant cell constituents by an isopycnic centrifugation in cesium chloride. Yelds of ac. 19,00 mg of virus was obtained per Kg of infected tissue. Polyacrilamide gel electrophoresis with sodium dodecyl sulfate of purified virus preparation revealed the presence of a main component protein with molecular weight of 36 kDa and a smaller protein component of 29 k, probably due to an enzymatic degradation of the capsidial protein during the process of purification and storage of the virus. The SrMV was transmitted efficiently by Aphis craccivora, in a non-persistent manner. The virus was not transmitted by 738 seeds from infected siratro plants. The obtained antiserum showed a titer of 1:16 for the virus, and a degree of specificity and a level of purify adequated to be used in double immune diffusion tests.